Total Factor Productivity Estimation in Peru: Primal and Dual Approaches - Céspedes, Nikita; Ramírez-Rondán, Nelson (Pontificia Universidad Católica del Perú. Fondo Editorial, 2014)
In this paper we estimate total factor productivity (TFP) growth for the Peruvian economy usingthe primal and dual methods for the period 2003-2012. According to the primal method, a procedure that uses the Solow residual as an indicator of productivity, TFP grew at an average annual rate of 1.6%, adjusted for the quality and usage of the factors of production. According to the dual method, a procedure that considers estimations of the marginal productivities of the factors of production, TFP grew at an annual rate of 1.7%.
Keywords: Productivity; Primal; Dual; Peru; Solow residual; https://purl.org/pe-repo/ocde/ford#5.02.01